A study to observe quantitative levels of C- Reactive Protein in Cerebrospinal fluid in patients with Meningitis as an add-on routine investigation- a case-control study - Manoj Kumar; Chandrashekhar Tiwari; Nandita Prabhat; Pooja Dhaon; Dharmendra Uraiya (International Journal of Medical Research and Review, 2021)
Introduction: C - reactive protein (CRP) is a member of the class of acute phase reactants as its level rises dramatically during inflammatory processes occurring in the body. Measuring and charting CRP values can prove useful in determining the disease progress. Aim: To estimate the CRP level in Cerebrospinal fluid (CSF) of patients with meningitis; and to evaluate whether CRP levels could be used to differentiate the various types of meningitis in adults. Materials and Methods: This study was a case-control study. 80 enrolled patients were subjected to a protocol that included detailed clinical history including duration of illness, symptoms and signs, history or any treatment history. Written informed consent was taken from the patients/guardian. Results: Meningitis was more common in the 18-30 years age group. Mean values of CSF CRP were- viral meningitis (2.70 mg/L) and pyogenic meningitis (91.13 mg/L) and control group (1.54 mg/L). CSF CRP can be used as a diagnostic tool to differentiate between pyogenic and viral meningitis as it is significantly raised in pyogenic meningitis in comparison to viral meningitis (p-value <0.0001). Conclusion: CRP in CSF is a valuable, rapid, bedside diagnostic test for differentiating between pyogenic and viral meningitis; with reasonably good sensitivity, specificity and positive predictive value. The absence of CRP in CSF rather than its presence is more important for the diagnosis of viral meningitis.